Aportes de nitrógeno y fósforo a cuerpos de agua de reservas urbanas, (Provincia de Buenos Aires) - Vigil, Gabriela (2022)
The contribution of nutrients to aquatic systems has been increasing simultaneously with the population increase. Urban and peri-urban nature reserves are fundamental spaces for the conservation of biological diversity and the preservation of a healthy environment. However, \nthe increase in human activities, the expansion of agricultural frontiers and urban growth, result in various environmental problems, such as eutrophication in their bodies of water, generated mainly by the contributions of Nitrogen (N) and Phosphorus (P), which are the nutrients most linked to the deterioration of aquatic ecosystems when they are in excess. \nThe Ecological Reserve El Renacer de la Laguna located in the Faculty of Veterinary Sciences (REFCV) of the UBA (FCV-UBA) and the San Antonio de Areco Parque Criollo (REPC) Nature Reserve, these are areas intended for environmental education and contact between the community and nature; however, they do not have management plans, which makes the comprehensive management of these protected areas difficult. The objective of this \nwork is to evaluate the contributions of N and P, and the degree of eutrophication of the lagoons of these two urban nature reserves, to prepare guidelines for the development of a future management plan for these water bodies. \nThe main results show that the values of Nt estimated and Pt in the Renacer de la Laguna lagoon range from 10.53 to 123.64 mg/L and from ?0.001 to 0.24 mg/L seasonally, while in \nthe Parque Criollo lagoon they vary from 25.19 to 49.56 mg/L and from 0.23 to 0.59 mg/L, respectively. The values of the N:P estimated molar ratios in the studied lagoons vary significantly from winter to summer, being the lagoon of the Parque Criollo the one with the lowest values. The lagoon of the REFCV presents a eutrophic state with a tendency to hypertrophic and the lagoon of the REPC a hypertrophic state throughout the different \nseasons of the year, trophic levels like the other pampasic lagoons, which triggers a series of\nenvironmental problems (hypoxic zones, harmful algal blooms, degradation of cultural and social values). The limiting nutrient in the lagoon of the REPC is N in all seasons, while in the lagoon of the REFCV can be both N and P, depending on the season of the year. \nThis study suggests the need to elaborate a management plan that allows executing guidelines \nand control measures that consider the quality of the water and the ecosystemic functioning of these lagoons.